Vaping on TikTok: a systematic thematic analysis. Issue 2 (26th July 2021) - Sun, Tianze; Lim, Carmen C.W.; Chung, Jack; Cheng, Brandon; Davidson, Lily; Tisdale, Calvert; Leung, Janni; Gartner, Coral E; Connor, Jason; Hall, Wayne D; Chan, Gary C.K.
Abstract : Introduction: The rising popularity of TikTok among adolescents may influence their awareness and perceptions of e-cigarette use via user-generated content. This study aimed to examine how e-cigarette/vaping-related videos are portrayed on TikTok. Methods: The nine most viewed hashtag based keywords were used to identify popular e-cigarette/vaping-related videos on TikTok (n=1000) from its inception (earliest upload date: January 2019) to November 2020. Five researchers independently coded the number of views, likes, user category and theme. Results: A final sample of 808 e-cigarette/vaping-related videos that met study criteria were included. Collectively, these videos were viewed over 1.5 billion times, with a median view count of 1 000 000 (range 112 900–78 600 000) and a median 'likes' count of 143 000 (range 10 000–1 000 000). A majority of the videos portrayed e-cigarette use positively (63%; collectively viewed over 1.1 billion times). Neutral depictions of e-cigarette use were viewed a total of 290 million times (24%) and negative depictions of e-cigarettes were viewed a total of 193 million times (13%). The video themes included (not mutually exclusively): 'comedy and joke' (52%; total of 618 million views), 'lifestyle and acceptability' (35%; 459 million), 'marketing' (29%; 392 million), 'vaping tricks' (20%; 487 million), 'nicotine and addiction' (20%; 194 million), 'creativity' (16%; 322 million) and 'warning' (11%; 131 million). Conclusion: Our findings illustrated that positively framed e-cigarette and vaping-related postings available without age restrictions on TikTok—a rising video-sharing platform that is popular among adolescents—have been viewed many times. Effective age restrictions are needed to reduce adolescents' potential exposure to videos that portray vaping positively.